Кубатурна формула для обчислення деякого класу сингулярних iнтегралiв - Назарчук, З.Т.; Кулинич, Я.П. (Видавничий дім "Академперіодика" НАН України, 2008)
A scheme to calculate a circular single layer potential is proposed. The cubature formulas use Gaussian weights and a value of Meijer’s G-function. The effectiveness of such an approach is shown.